Insomnia-related Memory Impairment in Individuals With Very Complex Chronic Pain. Issue 3 (September 2019) - Bothelius, Kristoffer; Hysing, Eva-Britt; Filén, Tove; Lundeborg, Linnea; Gordh, Torsten
Abstract : Objective: To investigate the specific effect of insomnia on neuropsychological functioning in patients with very complex chronic pain. Background: Individuals with insomnia disorder or chronic pain often experience cognitive deficits, with both conditions appearing to correlate with impairments in neuropsychological functions. As insomnia often occurs comorbid with chronic pain, distinguishing the differential effects of these two syndromes on an individual's neuropsychological functioning can be challenging. Comorbid depressive symptoms in these individuals, which may also affect cognitive function, may further obscure the associations between chronic pain, insomnia, and the neuropsychological profile. Methods: The neuropsychological function of 22 individuals with very complex chronic pain was assessed using specialized tests examining aspects of memory and executive functioning. The severity of insomnia, depression, and anxiety was measured using questionnaires, and pain levels were assessed using a visual analog scale. Pain medications were transformed to the morphine-equivalent daily dose. Results: Insomnia severity was found to predict memory function, accounting for 32.4% of the variance: A 1 SD increase in insomnia severity decreased memory function by 0.57 SD. The negative correlation between insomnia and memory was significant even after controlling for pain level, morphine-equivalent daily dose, and comorbid levels of anxiety and depression. Conclusions: Insomnia severity independently predicted memory function in patients with very complex chronic pain, even after controlling for other factors known to impair cognitive function. Insomnia may possibly explain some of the cognitive impairments related to chronic pain; thus, screening for, and treating, sleep disturbances may be a central aspect of chronic pain rehabilitation.